Murder in the Andamans: A Colonial Narrative of Sodomy, Jealousy and Violence - Manju Ludwig (South Asia Multidisciplinary Academic Journal)
This article will analyse colonial discourses on sodomy, jealousy and violence connected with the penal settlement of the Andamans in late 19th and early 20th century. The narrative in these files elucidates the incoherent ways in which colonial officials of different ranks tried to rationalise the phenomenon of same-sex behaviour by employing (pseudo-)scientific theories of criminality, race and climatic determinism. Moreover, the analysis tries to shed light on the manifold failures of the colonial regime in South Asia. The paper aims at contributing to the history of sexuality in colonial contexts by highlighting the role of colonial spaces as laboratories for emerging ‘European’ sexual theories.